Calculation of the Radionuclide Concentrations in Samples of Condiments by Using Gamma Spectroscopy System - Yaseen, Qabas A. J.; Subhi, Auday T.; Hadi, Ala A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of this work is to evaluate concentrations of natural and artificial radionuclide in nine different samples of condiments from local markets. The concentrations of 238 U , 232 Th ,40k and 137Cs were measured by using gamma spectroscopy with a high- purity germanium detector. The concentrations of 238 U, 232 Th ,40k and 137Cs were found to be in a range of (21.4 - 91.13), (15.7 - 88.11) , (285.56 – 1100) and (5.1 - 27.5) Bq.kg-1 respectively. These concentrations are not hazardous to public health and the activities are within the allowed levels